The Effect of Capital Structure and Ownership Structure on Financial Performance and Dividend Policy on Manufacturing Companies in the Indonesia Stock Exchange - Samira Hanim; Suhadak Suhadak; Nila Firdausi Nuzula (Sekolah Pascasarjana Universitas Brawijaya, 2018)
This study aimed to examine the effect of capital structure and ownership structure on financial performance and dividend policy. The study involved the manufacturing companies listed on IDX from 2012 to 2016. The data were analyzed by applying PLS (Partial Least Square). Research method used in this research was explanatory research using purposive sampling. The results of this study were: Capital Structure had a positive significant effect on Financial Performance, Capital Structure had non-significant effect on Dividend Policy, Ownership Structure had a positive significant effect on Financial Performance, Ownership Structure had non-significant effect on Dividend Policy, and Financial Performance had a positive significant effect on Dividend Policy.